9.4: Stretchable 45 × 80 RGB LED Display Using Meander Wiring Technology. Issue 1 (June 2015) - Ohmae, Hideki; Tomita, Yoshihiro; Kasahara, Mitsuhiro; Schram, Jeroen; Smits, Edsger; van den Brand, Jeroen; Bossuyt, Frederick; Vanfleteren, Jan; De Baets, Johan
Abstract : We present a str etchable and foldable passive matrix driven display using 45 by 80 RGB LED's mounted on a meandering printed circuitry embedded in a polyurethane film. The meander interconnections have been optimized with respect to their electrical and mechanical properties to provide a display with a 3 mm pitch between the pixels and a stretchability of up to 10%. At an operating supply voltage of 5 V, the brightness of the display exceeds 30 cd/m 2 .